The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/en11020263
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Electric Energy Storages and Thermal Energy Auxiliaries for Improving Wind Power Integration in the Cogeneration System

Abstract: Abstract:In regards to the cogeneration system in Northern China, mainly supported by combined heat and power (CHP) plants, it usually offers limited operation flexibility due to the joint production of electric and thermal power. For that large-scale wind farms included in the cogeneration system, a large amount of wind energy may have to be wasted. To solve this issue, the utilization of the electric energy storages and the thermal energy auxiliaries are recommended, including pumped hydro storage (PHS), com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…In the "showers" stage, hot water is used in the apartment's showers, washing machines, as well as bathroom and kitchen sinks. A heat exchanger (21; center-left area Figure 10) is used to obtain the hot water which is fed with saturated steam from the evaporator of the recovery boiler to achieve the hot water flow required for the building at 60 • C. Each process shaft (13,18,22,41,42) represents the hot water requirement for a section of the building, according to the number of people living in an apartment. The "hot air" stage is shown, which meets the needs of hot air by using a heat exchanger, where the hot water flow from the recovery boiler comes into contact, countercurrent wise, with the air that heats up from room temperature conditions on to 23 • C. Flows are separated per building and thereafter, the processes (30, 54, 56, 57 and 92) are distinguished according to living/dining room volume of <80 m 3 and between 80 and 144 m 3 .…”
Section: Choices Of Cogeneration Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the "showers" stage, hot water is used in the apartment's showers, washing machines, as well as bathroom and kitchen sinks. A heat exchanger (21; center-left area Figure 10) is used to obtain the hot water which is fed with saturated steam from the evaporator of the recovery boiler to achieve the hot water flow required for the building at 60 • C. Each process shaft (13,18,22,41,42) represents the hot water requirement for a section of the building, according to the number of people living in an apartment. The "hot air" stage is shown, which meets the needs of hot air by using a heat exchanger, where the hot water flow from the recovery boiler comes into contact, countercurrent wise, with the air that heats up from room temperature conditions on to 23 • C. Flows are separated per building and thereafter, the processes (30, 54, 56, 57 and 92) are distinguished according to living/dining room volume of <80 m 3 and between 80 and 144 m 3 .…”
Section: Choices Of Cogeneration Systemsmentioning
confidence: 99%
“…Such options obviously led to an improved system performance and reduced the environmental impacts; Buoro et al [21] identified the optimal energy production system and its optimal operation strategy required to satisfy the energy demand of a set of users in an industrial area. A distributed energy supply system is made up of a district heating network, a solar thermal plant with long term heat storage, a set of Combined Heat and Power units and conventional components also, such as boilers and compression chillers; and Yu et al [22] propose a general evaluation method to compare the performance of six different approaches for promoting wind power integration. In consideration of saving coal consumption, reducing CO 2 emissions, and increasing investment costs, the comprehensive benefits are defined as the evaluation index.…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to regulate the electric power flexibly because the heating demand has a priority to be met, especially during heating periods. 3 Hence, it is in urgent need to promote the flexibility of the power system for better utilization of wind energy.…”
Section: Introductionmentioning
confidence: 99%
“…Potential and performance evaluations of CAES have been mainly made by simulation tools or modelling processes in order to have energy and exergy results [9]. Indeed, the need of providing energy storage in system layouts for implementing the forthcoming smart energy systems concept [10][11][12] pushed researchers into trying different technological solutions at the prototype scale with a low technological readiness level [11], mainly from the pre-design of scenarios by means of comparative studies [13].…”
Section: Introductionmentioning
confidence: 99%